1998
DOI: 10.1200/jco.1998.16.1.70
|View full text |Cite
|
Sign up to set email alerts
|

Primary non-Hodgkin's lymphoma of the nose and nasopharynx: clinical features, tumor immunophenotype, and treatment outcome in 113 patients.

Abstract: The three immunophenotypes studied are shown to exhibit different clinical patterns. Since the NK/T phenotype carries the worst prognosis, patients who present with NNP-NHL should have their tumors analyzed for CD56 expression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
304
6
7

Year Published

2000
2000
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 408 publications
(329 citation statements)
references
References 43 publications
12
304
6
7
Order By: Relevance
“…16 Some studies in the Caucasian population also detected a strong but not invariable association with Epstein-Barr virus. 16,30 In extranasal sites, the association with the virus is more variable, 30 and Tsang et al 31 reported EBER expression in 62.5% of non-nasal CD56-positive TCLs. In this study, 96.7% of the cases of NK/TCL in the upper aerodigestive tract and all the tumors in the extranasal sites were positive for EBER.…”
Section: Survivalmentioning
confidence: 98%
See 2 more Smart Citations
“…16 Some studies in the Caucasian population also detected a strong but not invariable association with Epstein-Barr virus. 16,30 In extranasal sites, the association with the virus is more variable, 30 and Tsang et al 31 reported EBER expression in 62.5% of non-nasal CD56-positive TCLs. In this study, 96.7% of the cases of NK/TCL in the upper aerodigestive tract and all the tumors in the extranasal sites were positive for EBER.…”
Section: Survivalmentioning
confidence: 98%
“…Four cases were lost to followup. The patients were staged clinically according to the Ann Arbor system, 16 except for cases with skin tumors, which were staged according to the TNM staging of cutaneous TCL. 23 Survival was analyzed as a function of time from histologic diagnosis to the last date of follow-up in December 2002, using Kaplan-Meier product limit method.…”
Section: Clinical Findingsmentioning
confidence: 99%
See 1 more Smart Citation
“…Evidence of EBV has also been found in NK/T cell lymphoma [7]. They are rare and are mainly seen in Asia and Latin America.…”
Section: Discussionmentioning
confidence: 98%
“…These lymphomas have also been described in immunosuppressed and post-transplant patients [1]. They show a predominantly extranodal presentation, with the sites of predilection being the nasal cavity, and paranasal sinuses with extension into the nasopharynx, orbit, oral cavity, palate, and oropharynx [1,4]. Nasal lymphomas present as localized disease with symptoms such as nasal obstruction, discharge, or epistaxis due to the presence of a mass lesion, or with extensive midfacial destructive lesions (so-called lethal midline granuloma) [1,5].…”
Section: Diagnosis and Discussionmentioning
confidence: 99%